2022
DOI: 10.1155/2022/5389162
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Adiponectin Levels Are a Risk Factor for Cognitive Decline in Spinal Cord Injury

Abstract: Objective. Spinal cord injury (SCI) has become popular in recent years, and cognitive decline is a common complication. Adiponectin is a common protein hormone involved in the course of many diseases, but its relationship with SCI has not yet been elucidated. The purpose of our prospective study is to explore whether adiponectin can be used as a biomarker of cognitive decline in SCI. Methods. A total of 64 healthy volunteers and 92 patients with acute SCI were recruited by us. Serum adiponectin levels, demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Cognitive impairment is a widespread complication following spinal cord injury (SCI), affecting approximately 10-60% of patients [ 1 , 2 ]. Before the 1940s, only a small percentage of patients could survive for a few weeks after injury, but advances in technology have greatly improved the survival rate of SCI [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment is a widespread complication following spinal cord injury (SCI), affecting approximately 10-60% of patients [ 1 , 2 ]. Before the 1940s, only a small percentage of patients could survive for a few weeks after injury, but advances in technology have greatly improved the survival rate of SCI [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have demonstrated a relationship between systemic blood pressure and blood flow velocity and cognitive impairment following SCI ( Wecht et al, 2018 ). Our earlier research has demonstrated that neurogenesis, oxidative stress, and inflammation contribute to cognitive impairment following SCI ( Liu et al, 2022 ; Sun et al, 2021 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the injury comes from physical trauma, and more than half of all injuries affect the cervical spine ( 5 ). In the US, there are roughly 20,000 new instances of SCI each year, and the per-person lifetime economic cost can be as high as 3 million US dollars ( 6 , 7 ). The annual socioeconomic impact of SCI is projected to be 2.67 billion US dollars ( 8 ).…”
Section: Introductionmentioning
confidence: 99%